Oxidative fuel metabolism of ruff sandpipers (Philomachus pugnax) during cold exposure and exercise - Vaillancourt, Eric (University of Ottawa (Canada), 2005)
Indirect calorimetry and nitrogen excretion measurements allow quantifying dynamic changes in the rates of carbohydrate, lipid and protein oxidation over time. Although measuring oxygen consumption and carbon dioxide production is relatively simple, only a few studies presented these two measurements in avian models, but none used the data to calculate rates of metabolic fuel oxidation. Therefore, the first goal of this study was to use indirect calorimetry and nitrogen excretion measurements to quantify the rates of lipid, carbohydrate and protein oxidation over time in ruff sandpiper during cold exposure and terrestrial locomotion. Even though the data obtained does not allow me to test these hypotheses, one finding is really interesting. The ruff sandpiper may use intramuscular lipid reserves to power muscle contractions, but these small reserves would probably be depleted within a short period of time, especially during flight. Therefore, this species may have the capacity to use a secondary mechanism to carry lipids from the adipocytes to the working muscles. Because plasma albumin is present in limited amounts, and because each albumin molecule can only bind a limited number of fatty acids, VLDL-TAG from the liver may be a good way to insure that the working muscles do not run out of fuel. (Abstract shortened by UMI.)
Keywords: Biology, Ecology.; Biology, Animal Physiology.